Understanding the biomechanics of standing-up and sitting-down - Johnson, David (Department of Medicine, 2024)
Functional Neuromuscular Stimulation (FNS) has been shown to be effective in restoring certain upper and lower limb movements of spinal cord injured patients. The successful application of FNS to achieve standing-up and sitting-down, in persons with lower limb paralysis, depends largely on two factors: firstly, the torques generated at the hip, knee and ankle joints during these movements, and secondly, the extent and distribution of the accompanying muscular activity. With this knowledge it is possible to determine the electrical stimulation parameters and sequence required to restore the above movement in spinal cord injured patients. This thesis has a two-fold aim to study these two factors. A mathematical model to predict the torques generated at the hip, knee and ankle joints of individual participants was developed to achieve the first aim. This model is presented in the form of a computer program which requires anthropometrical and experimental data from the subject. The model was developed both from kinematic and kinetic aspects. The kinematic approach requires the varying angles at the hip, knee and ankle joints as inputs, whereas the kinetic approach requires the position of the ground reaction force in relation to the lateral malleolus, together with the ankle angles, as inputs. The various experiments performed to obtain the above mentioned variables are described. The second aim was achieved using electromyography to determine the sequential muscle activity, of the lower limb, during standing-up and sitting-down procedures. A description of the method used to obtain these electromyograms, together with a diagrammatic representation of the results, is presented. i1 As a result of the above mentioned theoretical modelling as well as simulation and validation experiments, the following conclusions can be made: (1) The mathematical model does predict reasonable torque values compared to that obtained in the literature. (2) The diagrammatic representation of the muscular activity is an acceptable reflection of the actual muscle activity. (3) In the light of the various problems encountered, a number of recommendations relating to both the mathematical model and the sequence of muscular activity are made